Exploring the experiences and challenges for patients undergoing cranioplasty: a mixed-methods study protocol. Issue 4 (22nd April 2022) - Mee, Harry; Clement, Clare; Anwar, Fahim; Whiting, Gemma; Timofeev, Ivan; Helmy, Adel; Hutchinson, Peter John; Kolias, Angelos G
Abstract : Introduction: Cranioplasty is a widely practised neurosurgical procedure aimed at reconstructing a skull defect, but its impact on a patient's rehabilitation following a traumatic brain injury (TBI) or stroke could be better understood. In addition, there are many issues that a TBI patient or the patient who had a stroke and their families may have to adapt to. Insight into some of the potential social barriers, including issues related to social engagement and cosmetic considerations, would be beneficial. Currently, little is known about how this procedure impacts a patient's recovery, the patient's perceptions of rehabilitation precranioplasty and postcranioplasty and the broader issues of cosmesis and social reintegration. This study hopes to understand some of these issues and therefore help inform clinicians of some of the difficulties and perceptions that patients and their relatives may have. Methods and analysis: A mixed-methods study. Data will be collected through focus groups with healthcare professionals (HCPs) and semi-structured interviews with patients and their relatives, field notes, a researcher diary and a patient questionnaire. Different perspectives will be brought together through method triangulation. Patient and relative data will be analysed using interpretive phenomenological analysis, and HCPs data will be analysed thematically using deductive and inductive coding. Ethics and dissemination: Ethical approval has been obtained from the Wales REC 7 ethics committee (Rec ref: 19/WA/0315). There is limited literature regarding a patient's perception of the cranioplasty process, the potential impact on rehabilitation and how this may impact their reintegration into the community. The results of this study will be presented at national brain injury conferences and published in peer-reviewed, national and international journals.